The review of concept image and concept definition: A hermeneutic phenomenological study on the derivative concepts - Prihandhika, Aditya; Perbowo, Krisna Satrio (International Journal of Didactic Mathematics in Distance Education, 2024)
Calculus classes often focus on studying derivatives, a fundamental topic in mathematics. Upon finishing their studies, potential mathematics teachers will educate students about advanced concepts such as derivatives in the classroom. Therefore, comprehending derivative concepts is essential for teaching children effectively. This study aims to determine how potential mathematics teachers view themselves concerning derivative concepts based on their concept image and concept definition. The study utilized a hermeneutic phenomenological approach together with qualitative approaches in its research strategy. The research data was obtained through interviews and clinical tests from six participants from one of the universities in Kuningan Regency, Indonesia. The research findings indicate that participants' concept image of derivative concepts is limited to symbolic representations. Most participants did not view derivative concepts as providing a deeper understanding but rather as a technique to solve procedural problems. The results indicate that utilizing a range of representations in the learning process can improve the development of a more thorough conceptual understanding, leading to better comprehension of derivative concepts.